Investigation of Annealing Conditions on Electrochemically Deposited CZTS Film on Flexible Molybdenum Foil. Issue 9 (1st January 2016) - Oliveri, R. L.; Ferrara, G.; Livreri, P.; Piazza, S.; Sunseri, C.; Inguanta, R.
Abstract : In this work, the electrodeposition of Cu2 ZnSnS4 thin films on molybdenum thin foil was reported. In order to guarantee co-deposition of elements with different standard electrochemical potential, an aqueous electrolyte added with ligand agents was used. I addition, deposition parameters were carefully chosen, in order to ensure good quality and suitable composition of the films. The deposited films were sulfurized in controlled atmosphere at 580°C, scrutinizing the influence of the annealing conditions on the features of the films. Structure, morphology and composition were investigated by XRD SEM, EDS and Raman spectroscopy. Results reveal the growth of good quality films, with a uniform morphology and chemical composition suitable for solar cell application.